Evaluating the Current Developments and Future Prospects of Agritourism: The Case of Cyprus. - Marneros, Stelios; Efstathiades, Andreas; Boukas, Nikolaos; Papageorgiou, George (My University, 2025)
This paper aims to investigate the prospect of agritourism in the island of Cyprus. For this purpose, primary research was carried out by collecting data through face-to-face in-depth interviews with managers/owners of a representative sample of agritourism establishments. Particular focus was placed on current developments and future scenarios of how agritourism can become an alternative sustainable form of tourism in the Cypriot tourism industry. Note that Mass tourism is currently frowned upon due to its negative effects. On the other hand, special interest or alternative tourism, could have fewer negative impacts on tourist sites and help battling the negative effects impact of mass tourism. In the case of agritourism tourists or otherwise visitors stay on farms, while at the same time participating in work related to agriculture or agricultural activity. It was found that this type of tourism can contribute both to the strengthening of the countryside and the elimination of some of the regional disparities. It is thus a form of sustainable tourism and it has now part of the development strategy of the European Union to support disadvantaged rural regions in countries where agriculture and farming occupy a small part of the GDP. The findings for the case of Cyprus provide entrepreneurs and tourism institutions, suggestions for the effective development of agritourism, that could also fill in the gap during the low demand seasonality periods and further support neglected rural communities.
Keywords: Hospitality management; Cyprus tourism; Agritourism; Alternative tourism; Special interest tourism; Sustainability